The Impact of Robot-Assisted Care on Cognitive Health and Mental Well-Being of the Elderly - Amit Shishodia (International Journal of Advanced Robotics and Automation Technology, 2025)
The rapid advancement of robotics and artificial intelligence (AI) has led to the development of robot-assisted care technologies, which are increasingly being deployed in elderly care settings. These robots are designed to provide physical assistance, emotional support, and cognitive stimulation for older adults. As the global population of elderly individuals grows, particularly in aging societies, it becomes increasingly important to explore innovative solutions that enhance the quality of life and well-being of this demographic. This paper reviews the impact of robot-assisted care on the cognitive health and mental well-being of the elderly, focusing on the potential benefits and challenges associated with robot use in caregiving environments. Through a detailed analysis of existing research, this article examines how robots can improve cognitive function, reduce symptoms of depression and anxiety, enhance social interaction, and provide personalized care. The paper also discusses the psychological and emotional effects of robot-assisted care, including the potential for robots to alleviate feelings of loneliness and isolation, which are prevalent among elderly individuals. Additionally, the challenges in the implementation and acceptance of robot-assisted care, such as ethical concerns, user acceptance, and the limitations of current technology, are addressed. This review concludes with recommendations for future research and development in robot-assisted elderly care, emphasizing the need for human-robot interaction models that respect the emotional and psychological needs of elderly individuals. The integration of robots in elderly care settings could play a crucial role in improving mental and cognitive health outcomes, ultimately fostering greater independence, and enhancing quality of life for the elderly population
Keywords: Cognitive stimulation; Pepper; Personal Robot; robot-assisted therapy; robots